A New Picture of Fire Extent, Variability, and Drought Interaction in Prescribed Fire Landscapes: Insights From Florida Government Records. Issue 15 (14th August 2018) - Nowell, H. K.; Holmes, C. D.; Robertson, K.; Teske, C.; Hiers, J. K.
Abstract: Florida, United States, government records provide a new resource for studying fire in landscapes managed with prescribed fire. In Florida, most fire area (92%) is prescribed. Current satellite fire products, which underpin most air pollution emission inventories, detect only 25% of burned area, which alters airborne emissions and environmental impacts. Moreover, these satellite products can misdiagnose spatiotemporal variability of fires. Overall fire area in Florida decreases during drought conditions as prescribed fires are avoided, but satellite data do not reflect this pattern. This pattern is consistent with prescribed fire successfully reducing overall fire risk and damages. Human management of prescribed fires and fuels can, therefore, break the conventional link between drought and wildfire and play an important role in mitigating rising fire risk in a changing climate. These results likely apply in other regions of the world with similar fire regimes. Plain Language Summary: Wildfires and prescribed (i.e., controlled) fires are major sources of air pollution, greenhouse gases, and aerosols. Accurately estimating emissions from fires is critical to understanding their impacts on the environment and for designing sound fire management policies. We show that for Florida, United States, current satellites—the primary tools for identifying the extent, location, and time of these fires—dramatically underestimate the amount of fire, poorly identify its variation in space and time and can mischaracterize its relationship to drought. Using government records of fires, where available, can overcome some satellite shortcomings and provide a more accurate picture of fire extent and variability. In Florida, these records show that land area consumed by fire decreases during drought conditions due to less prescribed burning, but this pattern is not detected by satellites. Similar results may be expected in other parts of the world with similar fire characteristics, including agricultural and savanna regions of South America, Africa, Europe, and Asia. Using prescribed fire can help land managers adapt to climate‐driven changes in wildfire activity. Key Points: Satellites detect only 25% of open biomass fire area and poorly resolve interannual fire variability in Florida and areas with similar fire regimes Fire area may decrease during drought in regions with extensive prescribed fire, like Florida, despite increases in wildfire Prescribed fires in the southeastern United States have a large day‐of‐week cycle that is missing from air pollutant emission inventories